Analisis Yuridis Terhadap Tindak Pidana Pencurian dengan Kekerasan yang Mengakibatkan Luka Berat (Studi Putusan Nomor 468/Pid.B/2025/PN Bgl) - Muhammad Enrico Pratama (PROGRESIF: Jurnal Hukum, 2026)
The criminal act of theft with violence is a form of crime against property accompanied by violence or threats of violence against the victim. This act not only causes material losses but can also result in physical and psychological suffering for the victim, especially when the violence leads to serious injuries. In the practice of law enforcement in Indonesia, the crime of theft with violence is regulated under Article 365 of the Indonesian Criminal Code (KUHP), which imposes heavier criminal sanctions compared to ordinary theft. The imposition of criminal sanctions on perpetrators must consider the elements of the criminal act, the available evidence, and the juridical considerations of the judges in order to realize legal certainty, justice, and legal benefit. This study aims to analyze the application of criminal law to the crime of theft with violence resulting in serious injury in Decision Number 468/Pid.B/2025/PN Bgl and to analyze the judges’ legal considerations in rendering the decision. This research uses a normative legal research method with statutory and case approaches. The data used are secondary data obtained through library research on laws and regulations, legal literature, and court decisions. The results of the study indicate that the application of Article 365 of the Indonesian Criminal Code in Decision Number 468/Pid.B/2025/PN Bgl is in accordance with the legal facts revealed during the trial, where the elements of theft accompanied by violence resulting in serious injury have been fulfilled. The judges’ considerations in rendering the decision were based on valid evidence, witness testimonies, the defendant’s statement, and the consequences suffered by the victim. Therefore, the judges’ decision is considered to reflect aspects of legal certainty and justice within society.